Evaluation of erythropoietin therapy in hemodialysis patients at PKU Muhammadiyah Hospital Yogyakarta - Adnan, Adnan; Dania, Haafizah; Supadmi, Woro (Universitas Ahmad Dahlan, 2018)
Most of the patients with end-stage renal disease who undergo hemodialysis receive erythropoietin (EPO) therapy for anemia treatment. Anemia with EPO deficiency is a common complication of chronic kidney disease (CKD). EPO therapy is expected to improve anemia and quality of life of patients. This analytic observational study was conducted in a cross-sectional design. It aimed to identify the difference in red blood cell profiles, namely hemoglobin (Hb), Mean Corpuscular Volume (MCV), Mean Corpuscular Hemoglobin (MCH), and Mean Corpuscular Hemoglobin Concentration (MCHC), and quality of life of CKD patients on EPO and non-EPO therapy at PKU Muhammadiyah Hospital in Yogyakarta. The inclusion criteria were PGK ICD N18.9 outpatients who received hemodialysis therapy at this hospital and were literate, able to understand the questionnaire, and willing to be a respondent. The results showed that there was no significant difference (p>0,05) between the red blood cells (Hb, MCV, MCH, MCHC) of the EPO and non-EPO therapy groups. The correlation between the EPO and the quality of life of patients in all of the KDQOL domains was p> 0.05. Aside from the insignificant difference between the EPO and non-EPO therapy groups, the research concluded that there was no correlation between either the EPO or the non-EPO therapy with the quality of life of hemodialysis patients.